Inhibition and Updating, but Not Switching, Predict Developmental Dyslexia and Individual Variation in Reading Ability - Doyle, Caoilainn; Smeaton, Alan F.; Roche, Richard A. P.; Boran, Lorraine (Frontiers in Psychology, 2018)
To elucidate the core executive function profile (strengths and weaknesses in inhibition, updating and switching) associated with dyslexia, address these common pitfalls, this study explored executive function in 27 children with dyslexia and 29 age matched controls using sensitive z-mean measures of each ability and controlled for individual differences in processing speed. This study found that developmental dyslexia is associated with inhibition and updating, but not switching impairments, at the error z-mean composite level, whilst controlling for processing speed. Dyslexia is associated with a switching strength at the reaction time z-mean composite level, however this is no longer significant whilst controlling for processing speed. Inhibition and updating (but not switching) error composites predicted both dyslexia likelihood and reading ability across the full range of variation from typical to atypical. The predictive relationships were such that those with poorer performance on inhibition and updating measures were significantly more likely to have a diagnosis of developmental dyslexia and also demonstrate poorer reading ability.. When reaction time composites were included in predictive models, only inhibition error composite is maintained as a predictor of reading ability. These findings suggest that inhibition and updating abilities are associated with developmental dyslexia and predict reading ability. In addition, these findings suggest that future studies should explore executive function training as an intervention for children with dyslexia as core executive functions appear to be modifiable with training and may transfer to improved reading ability.